1973
DOI: 10.1901/jeab.1973.19-113
|View full text |Cite
|
Sign up to set email alerts
|

RESPONDING MAINTAINED BY THE OPPORTUNITY TO ATTACK DURING AN INTERVAL FOOD REINFORCEMENT SCHEDULE1

Abstract: Pigeons responded in a two-key situation. Responses on the right key (food key) were reinforced with food presentation on a response-initiated fixed-interval schedule, (i.e., first response after a fixed period of time was reinforced); responses on the left key (target key) were reinforced on a fixed-ratio schedule (i.e., every nth response was reinforced) with the presentation of a target bird that could be attacked. When the interval value of the food reinforcement schedule was varied from 1 min to 5 min, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
2

Year Published

1977
1977
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 22 publications
6
36
0
2
Order By: Relevance
“…Rats showed more attack under the FR condition, suggesting that the response contingency was important and that attack was not simply a result of the stimulation. Other studies of schedule-induced attack (Cherek et al, 1973;Flory & Everist, 1977) have shown similar although less clear-cut effects of FR and FI contingencies. Perhaps other reinforcer-schedule contingencies (e.g., differential reinforcement of low rates) will be found to provide more clear-cut results.…”
Section: Home-cage Baselinementioning
confidence: 77%
See 2 more Smart Citations
“…Rats showed more attack under the FR condition, suggesting that the response contingency was important and that attack was not simply a result of the stimulation. Other studies of schedule-induced attack (Cherek et al, 1973;Flory & Everist, 1977) have shown similar although less clear-cut effects of FR and FI contingencies. Perhaps other reinforcer-schedule contingencies (e.g., differential reinforcement of low rates) will be found to provide more clear-cut results.…”
Section: Home-cage Baselinementioning
confidence: 77%
“…For this reason alone, the home-cage baseline is not a useful tool for assessing the contribution of reinforcer intermittency to schedule induction. Furthermore, the procedural differences (e.g., deprivation, session length) between a home-cage baseline and a corresponding experimental schedule condition could, under some circumstances, complicate the interpretation of results (Roper, 1981 (e.g., Falk, 1969;Flory, 1971), attack in pigeons (e.g., Cherek, Thompson, & Heistad, 1973), and distress calling in ducklings (e.g., Starr, 1978). In addition, responding is higher in the schedule than in the no-schedule condition.…”
Section: Home-cage Baselinementioning
confidence: 99%
See 1 more Smart Citation
“…Studies that have reported lower levels of induced behavior during response-independent schedules in either all or in some subjects have examined schedule-induced attack (Cherek et al, 1973;Flory & Everist, 1977;Huston & DeSisto, 1971). In one study taxi- dermically prepared targets were employed rather than live target pigeons (Flory & Everist).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported decreases (Cherek, Thompson, & Heistad, 1973;Flory & Everist, 1977;Huston & DeSisto, 1971), increases (Burks, 1970;Falk, 1961b;Flory & Everist, 1977;Schaeffer, Diehl, & Salzberg, 1966), or no difference (Azrin et al, 1966;Cherek et al, 1973;Flory & Everist, 1977) in induced responding during response-independent schedules than during comparable response-dependent schedules. The present study examined levels of induced attack during FR schedules, in which food presentation depended upon the completion of a fixed number of key pecks, with those levels generated during response-independent schedules matched for reinforcement frequency, in which the response key was covered and food was presented independent of responding.…”
Section: _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ _ __ _ _ _ _ _ _ _ _mentioning
confidence: 94%